What Do Central Bankers Do? Evidence from the European Central Banks' Executive Board - Harald Badinger; Volker Nitsch (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper examines how managers at the top of a public institution, central bank executives, allocate their working time. Using detailed information from personal diaries of the six members of the European Central Bank's Executive Board over a period of two years, we codify and analyze more than 3,700 reported activities and compare the results with recent findings on the time use of CEOs in the private sector. We report four additional observations. First, the daily schedule of central bankers is dominated by routine tasks; variations in economic uncertainty have, on average, no significant effect on the number of activities. Second, there are sizable differences in the scope of activities across board members. Third, the change in publication rules of diary entries from `on request' to `regular' was associated with a significant decline in reported activities. Fourth, nationality matters: Board members interact disproportionately often with fellow nationals.
Keywords: E02; E58; H83; 330; governance; management; time use